A Study of Pre-Christian and Christian Africa and Environmental Sustainability: A Reflection for the Church in Africa - Yaw Adu-Gyamfi (E-Journal of Humanities, Arts and Social Sciences)
Pre-Christian African communities were environmentally friendly. The communities developed taboos, myths, sayings and ethics, and enforced them to conserve, protect and nourish the environment for later generations. On the contrary, in spite of the Bible’s teachings about the need to conserve the environment, Christian African communities pollute the environment to a high rate of deterioration. The purpose of the study is to draw the attention of the Church in Africa to the level of filth resulting from failure to play her role in environmental sustainability and to provoke her into action. The study employed qualitative method to gather and analyse non-numerical data such as text for proper understanding of people’s own social reality, which included their beliefs, attitudes and motivation, and those of others. The phenomenological approach focussed on studying human experiences, particularly how individuals perceive and communicate their lived experiences. The discussions showed that pre-Christian Africa served as an effective agent of environmental sustainability than Christian Africa. It is recommended that African Christians change their hearts, take hermeneutics and theology seriously, promote environmental awareness, change their negative attitudes towards African environmental taboos and be careful of the wholesale borrowing of Western philosophy and science at the expense of traditional African beliefs and practices. The study concluded that the church in Africa has a duty to learn from pre-Christian African communities to help sustain the environment. The study has contributed towards scholars’ efforts to finding causes and possible solutions to environmental degradation in African communities and encourage African scholars to pay attention to traditional African methods of environmental issues.